Healthy individuals genetically at-risk for the development of Pemphigus vulgaris or Alopecia areata share disease-like cytokine dysregulation - Schwartz, Rebekah R.; Seiffert-Sinha, Kristina; Sinha, Animesh A. (Frontiers in Immunology, 2025)
Autoimmune diseases (AID) are defined by immune dysregulation characterized by specific humoral and/or cell mediated responses directed against the body’s own tissues. Cytokines in particular play a pivotal role in the pathogenesis of AID, with proinflammatory cytokines contributing to the initiation and propagation of autoimmune inflammation, whereas anti-inflammatory cytokines facilitate regression of inflammation and recovery from acute phases of the disease. Parallel work by our group evaluating a comprehensive set of pro- and anti-inflammatory serum cytokines in Pemphigus vulgaris (PV) as well as Alopecia areata (AA) uncovered a similar pattern of inheritance specific immune dysregulation in these two distinct autoimmune skin diseases. In AA, we found healthy control subjects who are blood related to AA patients exhibit the same cytokine dysregulation in Th1 and Th17 pathways as do patients with AA. In PV, patients as well as individuals who are healthy but yet carry certain PV-associated HLA alleles (termed here as HLA-matched controls) share a similar, but not fully overlapping pattern of cytokine expression that is distinct from control subjects who do not type for these HLA alleles. Specifically, PV patients as well as HLA-matched controls demonstrate immunological activation of several pro-inflammatory-, Th17-, Th2-pathway associated cytokines, and the chemokine IL-8. Thus, in both AA and PV, we reveal cytokine dysregulations that are linked to genetic background. The presence of disease promoting pathways in not only patients, but also genetically related, but healthy control individuals further evokes the novel hypothesis that there may be co-existing disease counteracting immune protective mechanisms at play in thwarting the threat of disease in genetically predisposed individuals who, despite harboring disease associated immune imbalances, remain healthy. Our data underscore the known tendency of AID to cluster in families and support the notion of the shared genetic/common cause hypothesis across multiple AID.